2023
DOI: 10.1002/zamm.202200213
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer through MHD Darcy Forchheimer Casson hybrid nanofluid flow across an exponential stretching sheet

Abstract: Recent research has reported on the energy and mass transition caused by Casson hybrid nanofluid flow across an extended stretching sheet. Thermal and velocity slip conditions, heat absorption, viscous dissipation, thermal radiation, the Darcy effect, and thermophoresis diffusion have all been considered in the study of fluid flow. Fluid flow is subjected to an angled magnetic field to control the flow stream. Cu and Al 2 O 3 NPs are dispensed into the Casson fluid to create a hybrid nanofluid (blood). The sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Chemically reactive flowing of magneto Carreau liquid driven to the stretched surface with joule heating and heat source/sink impacts: Darcy-Forchheimer model was demonstrated by Siddiq et al [18]. Thermal and mass transport along hydromagnetic Casson hybridity nanoparticle flowing through an exponentially stretched surface with the presence of Darcy Forchheimer scheme was presented by Alqahtani et al [19]. There is more updated research on Darcy Forchheimer mechanism in the refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemically reactive flowing of magneto Carreau liquid driven to the stretched surface with joule heating and heat source/sink impacts: Darcy-Forchheimer model was demonstrated by Siddiq et al [18]. Thermal and mass transport along hydromagnetic Casson hybridity nanoparticle flowing through an exponentially stretched surface with the presence of Darcy Forchheimer scheme was presented by Alqahtani et al [19]. There is more updated research on Darcy Forchheimer mechanism in the refs.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal and mass transport along hydromagnetic Casson hybridity nanoparticle flowing through an exponentially stretched surface with the presence of Darcy Forchheimer scheme was presented by Alqahtani et al. [19]. There is more updated research on Darcy Forchheimer mechanism in the refs.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported by Chandrasekar et al revealed that particle movement can be controlled under the effects of a transverse magnetic field with the injection process at the bottom and suction at the top of the channel. Studies on a variety of newly developed nanofluids composed of different basic fluids have been reported. In 2019, Waini et al achieved steady fluid flow with heat transformation through a porous shrinking/stretching surface. The results demonstrated that an increase in the volume fraction tends to decrease the skin friction values but enhances the values of the Nusselt number for both nanofluids and hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Mamatha et al [8] studied the Multi-linear regression of triple diffusive convectively heated boundary layer flow past a linear stretching sheet with suction and injection. Different studies were made on nanofluid flow past linear [Pradhan et al [9], Bilal et al [10], Chu et al [11], Li et al [12]], quadratic [Ramakrishna et al [13]] , exponential [Dey et al [14], Alqahtani et al [15]], slendering [Jayakar and Rushi Kumar [16]] and radial [Ibrahim and Gamachu [17]] stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…[14], Alqahtani et al. [15]], slendering [Jayakar and Rushi Kumar [16]] and radial [Ibrahim and Gamachu [17]] stretching sheet.…”
Section: Introductionmentioning
confidence: 99%